In Vitro Activity of Tedizolid, Dalbavancin, and Ceftobiprole Against Clostridium difficile - Binyamin, Dana; Nitzan, Orna; Azrad, Maya; Hamo, Zohar; Koren, Omry; Peretz, Avi (Frontiers in Microbiology, 2018)
Background: Clostridium difficile (C. difficile) is a major nosocomial pathogen that colonizes in the human gut. Recently, the U.S. FDA approved 3 new antimicrobial agents against gram-positive bacteria: Tedizolid, Dalbavancin, and ceftobiprole. The efficacy of these antibiotics for treatment of C. difficile infection has not been thoroughly examined. The current study aimed to examine the in vitro activity of these antibiotics against C. difficile. In addition, to compare between Dalbavancin and ceftobiprole to antibiotics from the same class: Vancomycin and ceftriaxone, respectively. Methods: Eighty-four C. difficile isolates were tested for susceptibility to Tedizolid, Dalbavancin, ceftobiprole, Vancomycin, and ceftriaxone by Etest technique in order to determine the minimum inhibitory concentration (MIC). Results: Upon comparison of the novel antibiotic agents, Dalbavancin demonstrated the lowest MIC values and ceftobiprole the highest at MIC50 (0.016 μg/mL, 0.38 μg/mL, and 1.5 μg/mL, for Dalbavancin, Tedizolid, and Ceftobiprole, respectively) and MIC90 (0.03 μg/mL, 0.78 μg/mL, and 3.17 μg/mL, respectively). Dalbavancin demonstrated significantly lower MIC50 and MIC90 values compared to Vancomycin (0.016 vs. 0.38 and 0.03 vs. 3.5, respectively) (p<0.001) and ceftobiprole had significantly lower MIC values compare to ceftriaxone (1.5 vs. 32 and 3.17 vs. 28.8, respectively) (p<0.001). Conclusion: Dalbavancin and Tedizolid may play a role as potential therapeutic agents for treatment of C. difficile infection. Examination of antibiotic effect on the intestinal microbiome and clinical trials are needed for more accurate results